PENGEMBANGAN MEDIA PEMBELAJARAN KARTU BERGAMBAR BERBASIS PETA KONSEP POKOK BAHASAN JAMUR DI SMP NEGERI 16 KOTA KUPANG TAHUN AJARAN 2018/2019 - Daud Serang; Fransina Th Nomleni; Paulus Tnunay (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2021)
ABSTRACT This study aims to develop a suitable picture card media product for use on the subject of mushrooms. The development model used in this study is the ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The presentation of the results of this study was obtained from the results of the test of material experts 94%, with good qualifications, design expert test 94%, media expert test 97%, small group test 79% and large group test 86%. Based on data from experts, it can be seen that according to material experts, design experts, media experts, small group trials and large group trials with the total number of presentations is 90%. The percentage of the assessment shows a positive response to the learning media for picture cards that are developed, thus indicating that the form of the image developed is suitable for use as a learning media because the form of learning media for picture cards is in accordance with the learning objectives. This is because the form of picture card Learning Media that has been developed has its own advantages, where the image characters contained in the picture card media can attract students' attention so that the learning material will be easier for students to understand and can help teachers to teach mushroom material.Keywords: Development, Learning Media, Picture Cards